The Effect of Systemic Nitroglycerin Administration on the Kynurenine Pathway in the Rat - Nagy-Grócz, Gábor; Laborc, Klaudia F.; Veres, Gábor; Bajtai, Attila; Bohár, Zsuzsanna; Zádori, Dénes; Fejes-Szabó, Annamária; Spekker, Eleonóra; Vécsei, László; Párdutz, Árpád (Frontiers in Neurology, 2017)
The primary headache disorders include migraine, which is one of the most frequent neurological disorders, which influences more than 14% of the whole population. Despite the research efforts, its exact pathomechanism is not fully revealed, but evidence points to the role of glutamate and its receptors. Kynurenic acid (KYNA) is an endogenous glutamate receptor antagonist produced by the kynurenine pathway (KP). Tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO) convert L-tryptophan to N-formyl-L-kynurenine, to be further transformed to L-kynurenine (L-KYN). Kynurenine aminotransferase-II (KAT-II), L-kynurenine hydrolase (KYNU) and L-kynurenine 3-monooxygenase (KMO) are key enzymes in the later steps of the KP. Nitroglycerin (NTG) administration serves as both human and animal model of migraine, causing the activation and sensitization in the trigeminal system. A previous study demonstrated a reduction of KAT-II expression following NTG administration in animals. The goal of current tests was to identify the potential modulatory effect of NTG on other metabolizing enzymes of the KP in the caudal trigeminal nucleus (TNC) of rats. Four hours following the intraperitoneal injection of NTG (10 mg/kg), the rats were perfused transcardially and the TNC was extracted for Western blotting. Western blot studies revealed that the expression of TDO2, IDO1, KYNU and KMO decreased in the TNC. The results demonstrated that NTG is able to down-regulate the KP, with a potential influence on the glutamatergic system as well, contributing to the development of trigeminal activation and sensitization in animals.